2008
DOI: 10.2188/jea.je2007388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Having a Sense of Purpose in Life on the Risk of Death from Cardiovascular Diseases

Abstract: BackgroundMany studies have focused on disease causality, but few of them deal with health-promoting factors. Thus, we examined the effect of having a sense of purpose in life (ikigai) on mortality from cardiovascular disease (CVD).MethodsIn 1988, we conducted a prospective cohort study of 2,959 Japanese subjects, ranging in age from 40 to 74 years, and followed them till the end of 2003. The level of their sense of purpose in life was evaluated by a self-administered questionnaire. After excluding those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 21 publications
4
44
2
2
Order By: Relevance
“…These findings mirror results from previous studies of adverse experience in identifying a similar set of target cells (34,36,41,42), with eudaimonic well-being in particular showing a reversal of CTRA-related transcription factor dynamics (12,33). These results identify specific psychological, cellular, and molecular targets for future analyses of the social signal transduction pathways that mediate the prospective health advantages of psychological well-being (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings mirror results from previous studies of adverse experience in identifying a similar set of target cells (34,36,41,42), with eudaimonic well-being in particular showing a reversal of CTRA-related transcription factor dynamics (12,33). These results identify specific psychological, cellular, and molecular targets for future analyses of the social signal transduction pathways that mediate the prospective health advantages of psychological well-being (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 85%
“…social genomics | gene regulation P sychological well-being has been shown to forecast future physical health above and beyond its association with current physical health (1)(2)(3)(4)(5)(6), and above and beyond its association with reduced levels of stress, depression, and other negative affective states (2,3,(5)(6)(7)(8)(9)(10)(11). However, the biological basis for this relationship remains poorly understood, in part because of a paucity of information regarding the molecular signaling pathways that transduce positive psychological states into somatic physiology (12), and in part because of the multidimensional nature of human well-being (6,13).…”
mentioning
confidence: 99%
“…The analysis by Tanno et al (2009) uses data for Japan and suggests that both men and women with sense of life purpose are less likely to die from any cause as well as from cardiovascular diseases in different follow-up intervals. Koizumi et al (2008) find lower mortality risk from cardiovascular diseases, but only for men, in another 15-year follow-up study for Japan.…”
Section: Mortalitymentioning
confidence: 80%
“…[13][14][15][16][17][18][19][20] However, the mechanisms by which psychological well-being affects health remain unclear. Pressman and Cohen 14 have suggested that positive affect has both direct and stress-buffering effects on health outcomes.…”
Section: Subdomain-specific Discussion Andmentioning
confidence: 99%